Focus and question formation in Edo - Thomas O. Omoruyi (Studies in African Linguistics)
The purpose of this study is to investigate the relations that hold between sentence constituents in focus constructions and the derivation of questions which involve focussing. We observe that word-order change plays a fundamental part in focussing as the elements in focus are moved to a sentence-initial position. As a result, these elements which are spoken about. questioned, or negated are made explicit. We examine the syntactic operations which occur when subject nouns. direct and indirect object nouns. genitival constructions. beneficiaries. locations. instruments and manner are focalized. Finally. we examine the derivational processes for polar and non-polar quesitons and the role focussing plays in eliciting appropriate responses from the hearers.